The use of precision farming technologies and crop in determining ecologically stable areas for organic production - Ласло, О. О.; Диченко, О. Ю. (Scientific Progress & Innovations, 2017)
The article examines the feasibility and need for precision farming technologies in the allocation of environmentally stable areas for the production of organic products. These results show that reducing the cost of obtaining a unit of quality agricultural products and reduce the burden on the environment are created and used precision technology system based on agronomic productivity.To achieve the objective should be clearly set criteria and standards for environmental areas, including not only the characteristics of the soil, but also human impact. The combination of new scientific technologies and the latest developments in the agricultural sector to develop a system enables precise production as a system of process improvement and crop farming, whose main task is the selection of environmentally sustainable raw material zones for the production of organic products.